INTERNALISASI NILAI RELIGIUSITAS PADA ANAK DALAM KELUARGA - Musa Alfadhil (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
Family is considered as the smallest community unit. There is no society without a family. This smallest community unit is where education learned for the child. Family is the most important place where the children form their potential, good morality, sense and skills, because of that it is really possible for parents to exert influence for their children. Furthermore, children as a mandate for parents need to be guided and monitored in order to bring them to behave and act according to Islamic regulation. It is because further education will depend on their basic education. The family also has a rule in giving the children Islamic education because the family is closely related to their lives. It can be said that if education in the family and the surrounding environment is good so it could be when the children grow up they will have good behavior.